Mathematical modeling - Kapur, Jagat Narain 1923-2002 (Mercury Learning and Information, 2023)
This book can be used in courses on mathematical modeling at the senior undergraduate or graduate level, or used as a reference for in-service scientists and engineers. The book aims to provide an overview of mathematical modeling through a panoramic view of applications of mathematics in science and technology. In each chapter, mathematical models are chosen from the physical, biological, social, economic, management, and engineering sciences. The models deal with differentconcepts, but have a common mathematical structure and bring out the unifying influence of mathematical modeling in different disciplines.FEATURES:- Provides a balance between theory and applications- Features models from the physical, biological, social, economic, management, and engineering sciences